Pentingnya Pendidikan Karakter di Era Digital untuk Masa Depan - Trisna Rukhmana; Aria Mulyapradana; Yosep Heristyo Endro Baruno; Karsim Karsim; Rizky Franchitika; Al Ikhlas (Journal on Education, 2024)
Character education is a crucial aspect in shaping the future of the younger generation, especially in the increasingly advanced digital era. However, the role of technology in shaping character and moral values ​​is becoming increasingly significant, with associated challenges and opportunities. This research explores the perceptions of education stakeholders regarding the importance of character education in the digital era, as well as the challenges and opportunities faced in integrating technology with character formation. Through a qualitative study using interviews and observations, the findings show the awareness that exists in the educational community regarding the importance of character education in the digital era. However, challenges in the use of technology are also acknowledged, including insufficient supervision and irresponsible use by students. However, technology also provides great opportunities in providing innovative and interesting character education. The implications of these findings highlight the need for strong collaboration between all educational stakeholders to maximize the potential of technology in shaping the character of the younger generation for a better future.